Transcranial theta-burst stimulation alters GLT-1 and vGluT1 expression in rat cerebellar cortex. (November 2016) - Mancic, Bojana; Stevanovic, Ivana; Ilic, Tihomir V.; Djuric, Ana; Stojanovic, Ivana; Milanovic, Sladjan; Ninkovic, Milica
Abstract: Repetitive transcranial magnetic stimulation (rTMS) induces changes in expression of proteins engaged in activity of excitatory and inhibitory systems as well as redox homeostasis. Our aim was to investigate the effect of single (SS) and repeated session (RS) of intermittent and continuous theta-burst stimulation (iTBS; cTBS) on the expression of vesicular and plasmatic glutamate transporters 1 (vGluT1 and GLT-1), glial fibrillary acidic protein (GFAP) and influence on oxidative status in rats cerebellar tissue and plasma. Redox state parameters in cerebellar tissue and plasma were assessed 24 h after single and 48 h after the last TBS session. Molecular changes were examined by immunofluorescence. Stimulation significantly increased thiol groups (SH) in tissue of SS iTBS group, and decreased in iTBS RS. Activity of glucose-6-phosphate-dehydrogenase (G6PD) was increased markedly in cTBS RS. Immunoreactivity of vGluT1 in cTBS RS decreased, while GLT-1 increased in cTBS SS and cTBS RS, compared to control. Present study gives insight in molecular and biochemical mechanisms by which iTBS and cTBS exerts its effects on rats cerebellar cortex. Highlights: Single iTBS increases GLT-1 expression in cerebellum. Repeated cTBS decreases vGluT1 expression in cerebellum. GFAP expression is unchanged in cerebellum due to single or repeated iTBS and cTBS. Applied TBS protocols do not lead to severe alteration of redox homeostasis.